Transitioning from high school to adulthood for persons with autism spectrum disorder - Roitsch, Jane (Henry Stewart Talks, 2025)
Autism Spectrum Disorder (ASD), Trajectories of ASD, Key characteristics, Challenges in ASD, Support services, TEACCH autism program, PEERS program